15 years of facts and figures on veterinary disciplinary measures in the Netherlands - Boissevain, Iaira E.; van Rooij, Myrthe; Jongbloed, A. W.; Meijboom, Franck L. B.; Hesselink, Jan Willem; Mandigers, Paul J. J. (Frontiers in Veterinary Science, 2022)
In most countries, a veterinary disciplinary system is in force to ensure the quality of the veterinary profession and to offer an objective platform for complaints. We present an analysis of 15 years of veterinary disciplinary verdicts (2001–2016) to compare facts and figures and identify which factors are of major influence on the outcome of the verdicts. Rulings were collected from both paper files and the digital database of the veterinary disciplinary council (VDC), categorized, and used to create a database that enabled a statistical analysis. The results showed that complaints pertaining to companion animals are filed predominantly by owners, whereas complaints about livestock are mostly filed by the governmental civil servant (CS). CS complaints mostly address compliance issues. For the complaints made by owners (client complaints, CCs), reporting, communication, and veterinary mistakes appeared to be of statistical significance. Further studies are needed to investigate the impact of the complaints on veterinarians in general and how we can improve the veterinary disciplinary system.